Synonymies in Ananas (Bromeliaceae) - Coppens D’eeckenbrugge, Geo; Govaerts, Rafaël (Phytotaxa, 2015)
To clarify the last pineapple classification, which only recognizes the tetraploid crownless A. macrodontes and the diploid A. comosus, with three cultivated and two wild botanical varieties, we re-establish A. comosus var. microstachys and revise ancient synonymies, underlining misinterpretations and distinguishing horticultural names from botanical names whenever possible.